Development of the Western Australian cancer nurse coordination service - Platt, V.; Plaster, M.; Jenkins, R.; Sykes, J.; Young, K.; Jackson, K.; Broderick, C.; Cooper, A.; Monterosso, Leanne (Cambridge Media, 2008)
The cancer care coordinator role is a rapidly emerging one, whose mandate is to achieve some potentially far-reaching reforms to systems of care. To ensure these developments realise their potential, it is timely to consider the most effective ways to design and implement models of care coordination that achieve the improvements being sought for the Australian cancer care system. The National service improvement framework for cancer delivered 19 critical intervention points, one of which addressed coordination of care. This recommended that people with cancer have a designated coordinator of care who knows about all aspects of their disease, treatment and support. The care coordinator will help people with cancer move between treatment components, and ensure they have access to appropriate information and support and that the treatment team is fully aware of a person's preferences and situation. This paper provides an insight into the development of the West Australian Cancer Nurse Coordination Service and a variety of the factors that have been considered and addressed in striving towards improving care coordination. Information about the West Australian health context and components of the role development to date will inform the reader of the complexity associated with this system reform.